Language, culture and community among urban Inuit in Ottawa - Patrick, Donna; Tomiak, Julie-Ann (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractThis paper discusses the social experiences and needs of an urban Inuit community in Ottawa, drawing on interview data gathered as part of collaborative research with the Ottawa Inuit Children’s Centre. Its aim is to trace the role of social, historical, and geographical processes in urban Inuit experiences and to assess how they must be considered in an analysis of Inuit language and culture programming needs in the city. Our findings support the notions that communities are not fixed or unified entities and that issues such as housing, language, and discrimination both unite and create barriers for Inuit in the city. Inuit-run language and culture programs are central to community-building and to increased access to employment and services in the city.